2011
DOI: 10.1039/c1ee01443a
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism behind the beneficial effect of light soaking on injection efficiency and photocurrent in dye sensitized solar cells

Abstract: Electrical and luminescence characterization was performed on 16 dye sensitized solar cells with different formulations, from different industrial and academic sources. Most of the cells were fabricated in pre-industrial pilot lines. The cells were put through a light soaking period up to 150 hours and then re-characterized. The results show the commonly observed increase in J sc with light soaking is due to a decrease in the conduction band energy (with respect to the electrolyte) and an increase in the injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 57 publications
4
77
0
Order By: Relevance
“…1c. A light soaking effect has been previously observed for TiO 2 based liquid electrolyte DSCs, 14,15,18,19 with the enhancement occurring over time periods ranging from hours to days to even months. However such phenomena are not usually observed in solid-state cells, and certainly not to the extent observed here, where the photocurrent more than doubles over the measurement time.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…1c. A light soaking effect has been previously observed for TiO 2 based liquid electrolyte DSCs, 14,15,18,19 with the enhancement occurring over time periods ranging from hours to days to even months. However such phenomena are not usually observed in solid-state cells, and certainly not to the extent observed here, where the photocurrent more than doubles over the measurement time.…”
Section: Resultsmentioning
confidence: 94%
“…This finding is interpreted to imply that enhanced electron transfer in that system is the mechanism behind the increase in photocurrent. 18 This correlation is surprising, not because of the inferred mechanism, but since the time-correlated single photon counting technique employed has a temporal resolution on the 100 ps timescale, which is much slower than the typical observed electron transfer rate of fs to ps.…”
Section: -29mentioning
confidence: 99%
See 1 more Smart Citation
“…These shifts occur when the acid/base characteristics of the electrolyte are changed intentionally, or change with time or light exposure. 41,42 . In DSSCs the shift in the capacitance curves has been assigned to adsorption/desorption of ions or dipoles that change the electric field between the TiO 2 and the electrolyte.…”
Section: Charge Density From Charge Extractionmentioning
confidence: 99%
“…28 Recently, a detailed study of this process using time-resolved luminescence on DSSCs prepared with ruthenium complex dyes and various electrolytes determined that the improved J sc observed after light exposure can be attributed to an increased injection yield arising from a change in the kinetics of injection caused by a positive conduction band shift. 29 This paper also reported a reduction in the charge recombination after light exposure to mitigate voltage losses from the conduction band shift. For DSSCs prepared from a zinc porphyrin dye we previously reported that a short light exposure treatment produced simultaneous improvements in the J sc , V oc and fill factor for a zinc porphyrin DSSC.…”
Section: Introductionmentioning
confidence: 98%